2002
DOI: 10.1034/j.1399-3046.2002.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile during rhGH therapy in pediatric renal transplant patients

Abstract: To evaluate the effect of recombinant human growth hormone (rhGH) treatment on the lipid profile of pediatric renal transplant patients, we studied nine children treated with rhGH for 1 yr and a control group of 12 untreated patients matched in terms of age, renal transplant function and post-transplant follow-up. The levels of lipoprotein (a [Lp(a)], cholesterol, triglycerides, apolipoprotein A (APO A) and apolipoprotein B (APO B), and the APO B/APO A ratio, were determined at baseline and after 6 and 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…There has been no report of diabetes mellitus development under rhGH, but one patient with cystinosis has been reported. Recombinant human growth hormone has also been found to induce an increase in lipoprotein(a) serum concentration without a significant change in cholesterol or triglycerides serum concentrations [82]. This increase did not persist over time after a long-lasting treatment with rhGH in patients with Turner syndrome [83].…”
Section: Management Of Growth Post-transplantationmentioning
confidence: 99%
“…There has been no report of diabetes mellitus development under rhGH, but one patient with cystinosis has been reported. Recombinant human growth hormone has also been found to induce an increase in lipoprotein(a) serum concentration without a significant change in cholesterol or triglycerides serum concentrations [82]. This increase did not persist over time after a long-lasting treatment with rhGH in patients with Turner syndrome [83].…”
Section: Management Of Growth Post-transplantationmentioning
confidence: 99%
“…Treatment with rGH has also been shown to improve linear growth in children after renal transplant. Randomized controlled trials performed to investigate the efficacy and safety of rGH use in growth-retarded transplant recipients demonstrated that rGH was consistently efficacious in improving the height velocity (HV) of renal transplant recipients (23)(24)(25)(26)(27)(28). Growth in the rGH-treated patients was increased by 7.7-9.0 cm/yr compared to 4.2-4.6 cm/yr in the control group in the two larger trials (25, 28) ( Table 2).…”
Section: Use Of Recombinant Growth Hormone Therapy After Renal Transpmentioning
confidence: 99%
“…Slipped capital femoral epiphysis, avascular necrosis, glucose intolerance, and pancreatitis have not been shown to be associated with growth hormone therapy (35). There had been no difference in cholesterol, triglycerides, and apolipoproteins although lipoprotein (a) levels have been higher in rGH-treated patients (27). Many clinicians prefer to wait 6-12 months after successful renal transplantation to fully evaluate growth and initiate rGH therapy.…”
Section: Safety Of Rgh Therapy After Transplantationmentioning
confidence: 99%
“…Intravenous infusion of acetylcholine and glyceryl trinitrate (nitroglycerin) significantly reduced PWV, by 6 -4% (p < 0.05) and 5 -2% (p < 0.01), respectively. [14] Growth hormone (GH) deficiency (GHD) predisposes individuals to an abnormal lipid profile and risk factors of the metabolic syndrome, including fibrinogen and plasminogen activator inhibitor, [15][16][17] which can adversely affect arterial endothelial function and increase APWV. [18,19] GHD is also liable to cause reduced skeletal muscle mass and strength, [20,21] contributing to reduced exercise capacity, [22] an altered substrate metabolism [23] and, therefore, reduced cardiac performance [22] with associated CVD.…”
mentioning
confidence: 99%